2013
DOI: 10.2209/tdcpublication.54.89
|View full text |Cite
|
Sign up to set email alerts
|

Estimated Percentile Curves of Occluding Pairs in an Adult Population

Abstract: The purpose of this study was to provide the estimated percentile curves of occlusal pairs (OPs) in adults for use in oral health instruction. Data on number of present teeth (PT) were obtained from the National Report on the Survey of Dental Disease in 2005. Data from 1,535 males and 2,248 females, ranging in age from 18 to 82, were analysed. The mean number of OPs were used from our previous report. In that report we can be estimated OPs from the number of PT. In this study, PT data were replaced by the mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
(23 reference statements)
0
2
0
Order By: Relevance
“…Patients who experienced such problems had 7-16 missing teeth and 7-8 occlusal contact points. Furthermore, Yoshino et al 20) reported the percentile curves of occlusal pairs (OPs) in adults. There appeared to be a cut-off point after 10 OPs where the percentile curves of OPs dropped off rapidly.…”
Section: Discussionmentioning
confidence: 99%
“…Patients who experienced such problems had 7-16 missing teeth and 7-8 occlusal contact points. Furthermore, Yoshino et al 20) reported the percentile curves of occlusal pairs (OPs) in adults. There appeared to be a cut-off point after 10 OPs where the percentile curves of OPs dropped off rapidly.…”
Section: Discussionmentioning
confidence: 99%
“…The causes of tooth loss are mainly caries, periodontal disease, trauma, and fracture 1,2,16) . In addition, tooth loss 4,5,7,10,18,21,22) and a decrease in occlusal support 7,15,20) have also been reported to be risks factors for tooth loss. As tooth loss is irreversible and increases with aging, the number of present teeth is frequently used as a measure in population-based epidemiological studies.…”
Section: Introductionmentioning
confidence: 99%